Food safety risk analysis frameworks adapted for use in informal value chains in low-and middle-income countries - CGIAR Research Program on Agriculture for Nutrition and Health (2019)
The framework has gone through several iterations and the most recent update was published in the Encyclopedia of Food Security and Sustainability.